Strategic management concepts & cases - Rothaermel, Frank T. (McGraw-Hill Irwin, 2013)
This new textbook, written with a single, strong voice, weaves together classic and cutting-edge theory with in-chapter cases and strategy highlights, to teach students how companies gain and sustain competitive advantage. OneBook...OneVoice...OneVision